High Concentrations of Sodium Chloride Improve Microbicidal Activity of Ibuprofen against Common Cystic Fibrosis Pathogens - Adrián J. Muñoz; Roxana V. Alasino; Ariel G. Garro; Valeria Heredia; Néstor H. García; David C. Cremonezzi; Dante M. Beltramo (MDPI AG, 2018)
Ibuprofen (IBU-H), a widely used anti-inflammatory, also shows a marked antimicrobial effect against several bacterial species, including those involved in cystic fibrosis such as Pseudomona aeruginosa, methicillin resistant Staphylococcus aureus and Burkholderia cepacia complex. Additionally, our results show significant synergy between water soluble Na-ibuprofen (IBU-Na) and ionic strength. Salt concentrations above 0.5 M modify the zeta potential promoting the action of Na-IBU; thus, with 1 M sodium chloride, IBU-Na is ten times more efficient than in the absence of ionic strength, and the minimum effective contact time is reduced from hours to minutes. In short time periods, where neither IBU-Na nor controls with 1 M NaCl show activity, the combination of both leads to a reduction in the bacterial load. We also analyzed whether the changes caused by salt on the bacterial membrane also promoted the activity of other microbicide compounds used in cystic fibrosis like gentamicin, tobramycin and phosphomycin. The results show that the presence of ionic strength only enhanced the bactericidal activity of the amphipathic molecule of IBU-Na. In this respect, the effect of saline concentration was also reflected in the surface properties of IBU-Na, where, in addition to the clear differences observed between 145 mM and 1 M, singular behaviors were also found, different in each condition. The combination of anti-inflammatory activity and this improved bactericidal effect of Na-IBU in hypertonic solution provides a new alternative for the treatment of respiratory infections of fibrotic patients based on known and widely used compounds.